Developing capacity in identifying cost-effective interventions to prevent and reduce obesity in China - Angela M. Jackson-Morris; Suying Chang; Christina L. Meyer; Guansheng Ma (Global Health Action)
Obesity is associated with multiple noncommunicable diseases and has increased rapidly worldwide. Population obesity in China grew fourfold between 1993 and 2015, increasing most rapidly among children and adolescents. Cost-effective policies and programs delivered over time and at scale are required to change this trajectory, yet application of methodologies to identify such interventions have been sparse. UNICEF China and Peking University together identified the need to strengthen the intervention evidence available to policymakers and to build stakeholders’ knowledge and skills. Investment cases combine a review of intervention evidence, policy landscape assessment, and economic modelling to identify cost-effective interventions suited to a specific context. A training and mentorship program aimed to build awareness, knowledge, and skills about this methodology to encourage its use to support decision making and planning to address obesity. Program participants reported increased knowledge of analytical methods to identify contextually relevant cost-effective obesity interventions (92% of evaluation respondents), and 82% reported increased knowledge of evidence-based obesity interventions. 79% reported confidence to apply the learning in their job roles. Training and mentorship can enhance stakeholder knowledge, skills, and confidence to apply investment case methodology to develop economic evidence to strengthen the basis of obesity policy and program commissioning.